New structure induced by elastic anisotropy in cylindrical nematic liquid crystal (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Basing on Landaude Gennes theory, this study investigated the chiral configurations of nematic liquid crystals confined to cylindrical capillaries with homeotropic anchoring on the cylinder walls. When the elastic anisotropy (L2/L1) is large enough, a new structure results from the convergence of two opposite escape directions of the heterochiral twist and escape radial (TER) configurations. The new defect presents when L2/L17 and disappears when L2/L1